Analysis of the Satisfaction of Narcotics Residents with Services at Nunukan Class IIB Correctional Facility - Maha Saputra, Hendra; Mujtahid, Iqbal Miftakhul; Nugroho, Rino A. (Fakultas Hukum Universitas Muhammadiyah Sorong, 2023)
This research aims to examine the satisfaction level of narcotics prisoners regarding the services provided at the Class IIB Nunukan Penitentiary. The research employs a qualitative research method, utilizing interview and literature review techniques. The data analysis technique utilized is qualitative data analysis, involving data presentation, data verification, data reduction, and the re-presentation of the reduced data. The results of the study indicate that inmates at Class IIB Nunukan Penitentiary are pleased with the caregiving and medical services that meet the standards of Law No. 12 of 1995. However, the service delivery faces hindrances such as budget constraints, inadequate facilities, limited transportation, and insufficient staff. Additionally, surveys and interviews reveal issues related to the non-objectivity and lack of empathy from officers, as well as insufficient communication between officers and inmates. Keywords: Satisfaction, Service, Prisoners, Correctional Institutions